Evolutionary law of the relatinship between Dongting Lake and three outlets of Jingjiang River in recent 60 years - Hu, GuangWei; Liang, YeWei; Ma, YiLan; Feng, HaiLi (Tecnología y ciencias del agua, 2024)
The Three Gorges Reservoir has begun to play a comprehensive role in power generation, flood control, shipping and other aspects, since June 1, 2003. Using long time series runoff and sediment transport data, the evolution of the relationship of the Dongting Lake and the three outlets of the Jingjiang River after operation of the Three Gorges Project was analyzed using Back Propagation neural networks, Mann-Kendall trend test, and double cumulative curves. The results show that: 1) On interannual and interdecadal scales, the decrease in runoff from Dongting Lake is mainly caused by the sharp decrease in runoff from the three outlets. To some extent, the siltation of the Dongting Lake was alleviated because of the reduction of sediment transport coming from the three outlets; 2) by analyzing the consistency of runoff and sediment transport in and out of Dongting Lake, it was found that the influence of the hydraulic engineering in the Yangtze River on runoff and sediment entering and leaving Dongting Lake is asynchronous. The rate of decay of sediment into the Lake is much greater than the decay rate of sediment out of the Lake; 3) from the trend change of the dried-up days of the three outlets, the three outlets tend to be silted, and the Ouchi River and the Hudu River gradually decline; 4) From the sedimentation process line of Dongting Lake, cumulative sedimentation of Dongting Lake from 2003 to 2018 was -2 829Ã—104 t, and the Dongting Lake changed from siltation state to erosion state; 5) a back propagation neural network model was used to simulate the runoff and sediment transport of Dongting Lake, and the results show that the simulation accuracy met the needs of Dongting Lake runoff and sediment transport prediction.